HUBUNGAN BERAT BAYI LAHIR RENDAH DAN PREMATURITAS DENGAN KEJADIAN IKTERUS NEONATORUM DI RSUD. PROF. DR. MARGONO SOEKARJO PURWOKERTO TAHUN 2014 - mariah ulfah (Universitas Harapan Bangsa Purwokerto, 2015)
Background: Cases of jaundice in Indonesia is still a problem in babies born especially in smallinfants (<2500 g at birth). Incidence of 50% in infants and 75% in infants less bulan.Kasus Prof. jaundice in the hospital. Dr. Margono Soekarjo Purwokerto In 2011 as many as 635 cases ofLBW BBLSR 135 cases and 32 cases. Objectives: To know the relationship between LBW and preamturitas against jaundiceNeonatorum in hospitals Prof. Dr. Margono Soekarjo Navan in 2011. Methods: The study was a descriptive correlation method with retrospective approach, thepopulation is 635 as neonatal jaundice Neonatorum, using sampling techniques quata samplingwith a sample of 100 neonates, the instrument used is the master table, and useful analysis ofdata using Kendall's tau. Results: No association was lbw to jaundice in the hospital Neonatorum Prof. Dr. MargonoSoekarjo Purwoerto In 2011 the value of p (Sig) 0.447. Prematurity No relation to neonataljaundice in the hospital mengami Prof. Dr. Margono Soekarjo Purwokerto In 2011 the value of p(Sig) 0.380. Conclusion: There was no association of LBW and prematurity in the hospital for jaundiceNeonatorum Prof. Dr. Margono Soekarjo Purwokerto Year 2011 Key words: : LBW, Prematurity and jaundice Neonatorum